2017
DOI: 10.3389/fimmu.2017.01225
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Leukocytosis Is Inversely Correlated with Intratumoral CD8+ T-Cell Infiltration and Associated with Worse Outcome after Chemoradiotherapy in Anal Cancer

Abstract: Peripheral blood leukocytosis has been implicated in promoting tumor progression leading to worse survival, but the mechanisms behind this phenomenon remain unexplored. Here, we examined the prognostic role of pretreatment white blood cell (WBC) count and clinicopathologic parameters in the context of CD8+ tumor-infiltrating lymphocytes (TIL) and myeloperoxidase+ tumor-associated neutrophils (TANs) in patients with anal squamous cell carcinoma (ASCC) treated with definitive chemoradiotherapy (CRT). After a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
7
27
0
Order By: Relevance
“…Even more, chronic inflammation was supposed to lead to the development of various malignant lesions and to the increasing risk of relapse ( 12 ). So in line with our results, baseline leukocytosis displayed a worse prognosis in oropharyngeal cancer ( 7 ), anal carcinoma ( 8 , 13 ) and cervical cancer ( 9 ). Neutrophils are the most majority of peripheral leukocyte and are the first reaction responding to sites of inflammation and progression.…”
Section: Discussionsupporting
confidence: 90%
“…Even more, chronic inflammation was supposed to lead to the development of various malignant lesions and to the increasing risk of relapse ( 12 ). So in line with our results, baseline leukocytosis displayed a worse prognosis in oropharyngeal cancer ( 7 ), anal carcinoma ( 8 , 13 ) and cervical cancer ( 9 ). Neutrophils are the most majority of peripheral leukocyte and are the first reaction responding to sites of inflammation and progression.…”
Section: Discussionsupporting
confidence: 90%
“…Also, a combined leukocyte-CEA score revealed that classified patients into three risk groups showed strong correlation with clinical outcome. Our data are in line to previous reports indicating an unfavorable role of peripheral blood leukocytosis and neutrophilia in the context of inflammation in different malignancies, [12][13][14][15][16][17][18]21 including rectal cancer. 22,23 With regard to NLR, a pooled analysis of retrospective studies indicated a negative predictive impact in rectal cancer.…”
Section: <0001supporting
confidence: 93%
“…11 Although several groups have reported the unfavorable prognostic impact of peripheral blood leukocytosis and/or neutrophilia in patients with various malignancies, also in the context of neutrophil-to-lymphocyte ratio (NLR), these studies were limited by their retrospective nature, inhomogeneous treatment regimens and small patient numbers. [12][13][14][15][16][17][18] In the present secondary analysis, we examined the prognostic role of peripheral blood leukocytes and neutrophils together with other markers, including hemoglobin, platelets, lactate dehydrogenase (LDH) and carcinoembryonic antigen (CEA), in a large cohort of patients with rectal cancer (n = 1,236) treated within the CAO/ARO/AIO-04 phase 3 randomized trial. 19 In that trial, the addition of oxaliplatin to 5-FU-based preoperative CRT resulted in a significant improvement of the primary endpoint, DFS, compared to the standard arm.…”
Section: Introductionmentioning
confidence: 99%
“…The explanation for the favorable clinical outcome of chemoradiotherapy in HPV16 positive patients is evident in tumors harboring strong infiltration of immune cells. These tumors present tumor-infiltrating lymphocytes (TILs) with a strong expression of CD8 and the immunological markers Programmed Cell Death Protein-1 (PD-1) and its ligand (PD-L1) [ 44 , 45 ] Patients with SSC of the anal canal with high levels of infiltration of TILs present a relapse-free rate higher than those with low levels of infiltration of TILs [ 46 ]. For this reason it is important that the immune recognition in SSC of the anal canal is measured systemically.…”
Section: Discussionmentioning
confidence: 99%